Kinematics Analysis of Working Devices of Wheel Loader based on Homogeneous Coordinate Transformation - 臧红彬; 陶俊杰; 张辉 (Jixie chuandong)
The kinematics equation of working devices is established by using the homogeneous coordinate transformation,and this is a new way for studying kinematics and dynamics of the working device of loader.Firstly,the kinematics equation of working devices is established by analyzing the structure and operation process of working device,drafting the coordinate rotation point path using homogeneous coordinate transformation,and solving the rotation angle.Secondly,the virtual prototype model of the working device is built in ADAMS and the kinematics simulation is analyzed.Then the kinematics equation of working devices is verified according to the analysis of the calculation data of kinematics equation and the virtual prototype data.